Optical Fiber Sensors for Metal Ions Detection Based on Novel Fluorescent Materials - Cai, Yi; Li, Ming; Wang, Minghao; Li, Jin; Zhang, Ya-nan; Zhao, Yong (Frontiers in Physics, 2020)
Recently, novel fluorescent probes based on biomaterials and luminescent nanomaterials for metal ions attract tremendous attentions, owing to their advantages of simple operation, high sensitivity and rapid response for metals detection. Immobilized on the optical fiber sensor, fluorescent probes reveal the advantages while facing outdoor detection challenges. Therefore, numerous fluorescent optical fiber sensors for metal ions have been developed for online and in-situ detection to predict and prevent the environmental problems. Differ from refractometer-based fiber sensors, the structures of the fiber sensors based on fluorescent materials are usually simple, and the characters of the materials and the fabrication processes of fiber sensors are more significant to the sensing performances. This paper summarized the studies of optical fiber sensors for metal detection based on novel fluorescent materials to help researchers get the highlights of recent notable advancements and obtain the better potential prospects.